Examining the impact of managerial coaching on employee job performance: Mediating role of work engagement, leader-member-exchange quality, job satisfaction, and turnover intentions - Muhammad Ali; Suleman Aziz Lodhi; Orangzab; Basharat Raza; Wasif Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Coaching is turning into a vital area for human resource development experts. Human resource development professionals, researchers, training related experts and organizational psychologists have started to explore intensively the nature of managerial coaching and its outcomes. Managerial coaching has become a very popular human resource development and organizational development tool to improve various employees' attitudes and behavior at workplace. The managerial coaching lacks empirical evidence regarding its effectiveness. This study aims to examine the direct influence of managerial coaching on employee job performance as well as indirect influence through mediating effect of work engagement, leader-member-exchange quality, job satisfaction, and turnover intentions. The data were collected from a public-sector organization of Pakistan. The self-administered questionnaires were used to collect data from 183 respondents. The Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis showed that managerial coaching directly influences employee job performance. The path analysis also revealed that managerial coaching indirectly effects job performance through work engagement, leader-member-exchange quality, job satisfaction, and turnover intentions. This study adds value to limited literature on managerial coaching, leader-member-exchange quality, work engagement, and job performance. Additionally, leader-member-exchange quality and work engagement have not previously been examined as mediators. The implications for research, theory, and practice are also discussed.
Keywords: 330; managerial coaching; job performance; work engagement; leader-member-exchange quality; job satisfaction; turnover intentions